Evaluation of bone repair of defects treated with Bio-Oss® and platelet rich fibrin (PRF) - Suarez, Eduardo Antonio Chelin; Torquato, Leticia Cavassini; Mantovani, Ludmilla Oliveira; Pereira, Kauê Alberto; Maciel, Clarissa Carvalho Martins; Almeida, Nataly Domingues; Nunes, Camilla Magnoni Moretto; Jardini, Maria Aparecida Neves; Santamaria, Mauro Pedrine; de Marco, Andrea Carvalho (Brazilian Dental Science, 2026)
Objective: The aim of this study was to evaluate the bone repair of critical size defects in rats treated with bovine bone matrix (Bio-Oss®) and platelet, and leukocyte-rich fibrin (L-PRF) through histomorphometric and Immunohistochemical analysis. Material and Methods: Thirty adult rats (Albinus, Wistar), 90 days old, were used. Two critical bone defects of 5mm in diameter were made in the calvaria. The animals were divided into 4 (four) groups: those with C-Blood clot, B-Bio-Oss®, PRF-PRF, B+PRF-Bio-Oss®+PRF. Each group was subdivided into observation periods of 30 and 60 days. All data were statistically analyzed, with a significance level of 5%. Results: All groups presented similar results regards the proportion of bone neoformation. At 30 days, in the proportion of lamellar neoformation, PRF showed a statistical difference with B (Bvs.PRF, p=0.0256). Regarding the closure of the defect, at the 30 days mark the PRF showed a difference from C (PRFvs.C, p=0.0374), and at the 60 days, the B showed difference to GC (Bvs.C, p=0.0374). summarize the article’s main findings. Conclusion: Through descriptive statistics, it was possible to observe that FRP has a positive action on the initial bone neoformation process. The association Bio-Oss® and PRF seems to be related to the maintenance of the bone neoformation architecture. However, more studies are needed to confirm this finding.KEYWORDSBiocompatible materials; Bone regeneration; Osteogenesis; Platelet rich fibrin; Tissue engineering.